POPULASI DAN INTENSITAS SERANGAN HAMA KUMBANG TANDUK (Oryctes rhinoceros Linn.) PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) BELUM MENGHASILKAN - Joni Handoko; Hafiz Fauzana; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Research of aims to determine the intensity attact of pest populations O. rhinoceros on plant oil palm (Elaeis guineensis Jacq.) Immature. The research was conducted at PT. Inecda Plantation Tani Makmur village subdistrict of Rengat BaratIndragiri Hulu in February-March 2016. The study was a survey research using purposive sampling method to determine swath systematic sampling to determine the plant samples. The Parameter was description of the research sites, O. rhinoceros flyblow, population of O. rhinoceros bettle and intensity of pest attacks O. rhinoceros. The results were obtained flyblow population of 1.6 O. rhinoceros, O. rhinoceros beetle population as much as 58.16 tail / ferotrap / week and intensity pest attacks of 22.76% , Keywords: O. rhinoceros Linn, plant oil palm, the intensity of the attacks